Faktor Penghambat Perlibatan Dan Pemberdayaan Karyawan Implementasi Pelibatan Dan Pemberdayaan Karyawan Penghargaan Karyawan Dan Pengakuan Prestasi Karyawan - Yeni Lestari; Eka Indah Rahayu Putri; Shiddiqah Taqiya; Ali Murtopo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Involvement and empowerment in quality is a series of ongoing activities, the implementation of which requires a significant amount of time, energy and costs. Inclusion and empowerment are closely related to the behavior of human resources in the organization. The type of research used is library research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. In today's competitive business environment, employee empowerment has become an important concept in human resources. The employee empowerment process allows employees to play an active role in decision making in an organization to increase the alignment of personal goals with organizational goals.